1992
DOI: 10.1135/cccc19920001
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interconversion of Isomers of [16]annulene by the AM1 Method

Abstract: The AM1 method was used to carry out a theoretical study of different isomers of [16]annulene and of the reversible transformation between them preserving the molecular periphery. Transition states were located on the corresponding potential energy hypersurface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
7
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…The best one, 14 , is only 6.2 kcal/mol higher in energy than 13 and exhibits significant aromatic character (Table ). The relative energies of 13 − 16 correlate with the average deviations of the CCC angles from the strain-free 124.3° value . In accord with Heilbronner's expectation, 14 has the least amount of angle strain and (with the exception of 11 ) the greatest degree of bond-length equalization of all the Möbius annulenes reported here.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The best one, 14 , is only 6.2 kcal/mol higher in energy than 13 and exhibits significant aromatic character (Table ). The relative energies of 13 − 16 correlate with the average deviations of the CCC angles from the strain-free 124.3° value . In accord with Heilbronner's expectation, 14 has the least amount of angle strain and (with the exception of 11 ) the greatest degree of bond-length equalization of all the Möbius annulenes reported here.…”
supporting
confidence: 85%
“…Clearly aromatic stabilization is not great enough to overcome the strain associated with the different conformations. In 1991, Hernando and co-workers found that “valence angle strain” determined the relative AM1 stabilities of the known [16]annulenes …”
mentioning
confidence: 99%
“…Confirming the intuitive observation, it was found that Hernando et al, using semiemperical calculations, had already predicted the existence of these isomers of [16]annulene. The aforementioned authors further indicate that the two isomers have slightly different energies, the most stable of each pair having relatively more ideal bond angles . As the temperature of the [16]annulene system is lowered, the energetically allowed geometry of the σ-framework approaches ideality (120° C−CC bond angles).…”
supporting
confidence: 59%
“…From the 1 H NMR data, it is apparent that in both the [16]- and [18]annulenes, there must exist such lower-energy structures having σ-frameworks that enforce greater π-delocalization and thus greater ring current (paratropic in the 4 n π-electron system and diatropic in the 4 n + 2 π-electron system).
3 The conformers (A, B, C, and D) for [16]annulene that were proposed by Hernando are shown (ref ). The plus signs indicate that the proton extends forward from the plane of the molecule, while a minus signifies that it extents back into the page.
…”
mentioning
confidence: 99%
See 1 more Smart Citation